Association of Atrial Fibrosis Quantified Using LGE‐MRI with Atrial Appendage Thrombus and Spontaneous Contrast on Transesophageal Echocardiography in Patients with Atrial Fibrillation. (11th July 2013) - Akoum, Nazem; Fernandez, Genaro; Wilson, Brent; Mcgann, Christopher; Kholmovski, Eugene; Marrouche, Nassir
Atrial Fibrosis and Appendage Thrombus Introduction Transesophageal echocardiography (TEE) is used to evaluate for left atrial appendage (LAA) thrombi prior to restoration of sinus rhythm in atrial fibrillation (AF). We examined the relationship of atrial fibrosis quantified using late gadolinium enhancement MRI (LGE‐MRI) with TEE findings. Methods and Results We included 178 patients with AF, undergoing TEE and LGE‐MRI prior to ablation or cardioversion. LGE‐MRI and subsequent image processing was used to quantify atrial fibrosis based on signal intensity analysis. The mean CHADS2 score was 1.24 ± 1.08 and CHA2DS2‐VASc was 2.08 ± 1.33. The LAA was classified as normal, spontaneous echocardiographic contrast (SEC) present or thrombus present. LAA thrombus was found in 12 patients (6.7%) while SEC was identified in 19 patients (10.7%). Patients with thrombus had higher atrial fibrosis compared to patients without thrombus (26.9 ± 17.4% vs 16.7 ± 10.5%; P < 0.01). Atrial fibrosis was also higher in patients with SEC (23.3 ± 13.7%) compared to those without SEC (16.7 ± 10.8%; P = 0.01). Patients with high atrial fibrosis (>20%) were more likely to have a LAA thrombus (odds ratio 4.6; P = 0.02) and SEC (odds ratio 2.6; P = 0.06). Multivariate logistic regression showed high fibrosis (odds ratio 3.6; P < 0.01) and CHADS2 ≥2 (odds ratio 3.5; P < 0.01) were significant predictors of TEE abnormalities (LAA thrombus or SEC). The area under the curve for the model including high fibrosis, AF type and CHADS2 ≥2 or CHA2DS2‐VASc ≥2 was 0.73 compared to 0.63 and 0.65 for CHADS2 and CHA2DS2‐VASc alone. Conclusions Atrial fibrosis is independently associated with appendage thrombus and spontaneous contrast. It provides additional risk stratification not captured by clinical parameters.